IMPLEMENTASI MODEL PROBLEM BASED LEARNING PADA MATERI GERAK MENGGELINDING TERHADAP PENINGKATAN HASIL BELAJAR PESERTA DIDIK - Antameng, Johan Olden B.; Komansilan, Alfrits; Polii, Jefferson; Lahope, Kenny Setiawan (LPPM Politeknik Saint Paul Sorong, 2024)
Implementation of Problem Based Learning Model on Rolling Motion Material to Improve Students' Learning Outcomes. Thesis. Department of Physics. Faculty of Mathematics and Earth Sciences. Tondano. 2024. The problem in this study is that physics learning, especially in rolling motion material on an inclined plane, is done theoretically without so that students lack understanding of the material and the use of an inappropriate learning model that has an impact on the average score of students less than sixty-five, in other words insufficient. This study aims to examine the improvement of student learning outcomes with a problem-based learning model. The population of this study amounted to 240 students of class XII SMA Negeri 2 Bitung with a sample of 1 class for the experimental class and 1 class as a control class, each of which amounted to 25 people. This research method is quantitative. Data in this study were collected using pretest-posttest questions. Based on the discussion presented in this study in the previous section, it can be concluded that there is an increase in the learning outcomes of students on rolling motion material on an inclined plane with the Problem Based Learning model at SMA Negeri 2 Bitung.